Comparative Histological Study of the Stomach in Two Species of Iraqi Vertebrates (Magpie Pica pica L. and Small Asian Mongoose Herpestes javanicus E.) (Baghdad Science Journal, 2019)
A histological study showed the wall of the stomach in Pica pica and Herpestes javanicus consists of four layers: mucosa, submucosa, muscularis externa and serosa. Also, the present study showed many differences in the histological structures of the stomach for each in both types. The stomach of P. pica consists of two portions: the proventiculus and gizzard, while the stomach of H. javanicus consists of three portions: cardiac, fundic and pyloric regions. The mucosa layer formed short gastric folds, named plicae. In the proventiculus of P. pica, sulcus is found between each two plicae, but the folds called gastric pits in the gizzard, which are full with koilin. Lamina properia in both types contained gastric glands (straight simple tubular glands) named superficial glands, as well as another gastric gland found in the submucosa layer of the proventiculus in P. pica only named deep gastric glands. The gastric gland in the stomach of H. javanicus contained: mucous neck cells and parietal cells positive to AB/PAS stains in cardiac portion, as well as chief cells in fundic portion, but pyloric portion had just mucous neck cells. Muscularis externa in both types formed two muscle layers: inner and outer layer.